Efficacy assessment of radiosynoviorthesis on the progression of radiological osteoarthritic features of hip and ankle joint in patients with osteoarthritis and rheumatoid arthritis - Szerb, Imre; Gál, Tamás; Kiss, Dániel; Nagy, Viktória; Hangody, László (Nuklearmedizin - NuclearMedicine, 2020)
Objective The study objective was to evaluate the long-term effect of radiosynoviorthesis (RSO) on the progression of radiological and nuclear-medical osteoarthritic features of hip and ankle joint in patients with osteoarthritis and rheumatoid arthritis.Patients and Methods The study included 89 hip joints of 81 patients, of which 48 had osteoarthritis (OA) and 33 had rheumatoid arthritis (RA). In terms of ankle joints, 64 patients were included of which 43 suffered from OA and 21 from RA. The mean follow-up time was 9.2 years for OA and 8.9 years for RA patients. Patients with RA were the active control group. Structural alterations of the hip joints were evaluated following Kellgren-Lawrence score and of ankle joint following Takakura score for both disease entities. For the evaluation of synovitis 2-phase bone scintigraphy was performed.Results RSO could prevent radiologic status deterioration among 70.6 % of hip osteoarthritic patients and 73.7 % among the hip RA patients. No structural progression was observed in 79.1 % of the treated ankle joints in patients with OA and in 85.7 % of the ankle joints in patients with RA.The scintigraphic response rate for the hip joints of OA patients was 68.6 %, 76.3 % for hip joints of RA patients, 83.1 %, ankle joints of OA patients, and 90.4 % ankle joints of RA patients.The radiographic and scintigraphic RSO response rates were not significantly higher for both joints in RA than OA patients.Conclusion RSO can be a good alternative in the treatment of synovitis and prevention of deterioration of inflammatory and radiographic features even in patients suffering from osteoarthritis and rheumatoid arthritis. RSO may have also a long-term effect to stop or delay progression of both diseases.
Keywords: osteoarthritis; rheumatoid arthritis; radiosynoviorthesis; synovitis